2022
DOI: 10.1089/whr.2021.0140
|View full text |Cite
|
Sign up to set email alerts
|

The Multimodal Ultrasound Features of Ovarian Serous Surface Papillary Borderline Tumor

Abstract: Aim: Ovarian serous surface papillary borderline tumor (OSSPBT) is very rare. Combined with clinical and pathological features, we aim to investigate the multimodal ultrasound features of OSSPBT. Patients and Methods: There were only 18 patients diagnosed with OSSPBT among the 142 patients who were diagnosed with borderline serous ovarian tumor by pathology from June 2008 to December 2020 in our hospital. Their clinical data, conventional ultrasound, two-dimensional con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Morotti et al reported that serum CA 125 level was elevated in 24-61% of patients with SBOT 16 . In the study of Xie et al 14 , 83.3% of patients with SSPBOT presented with variously high levels of CA 125. The difference may be attributable to the varying proportions of patients with advanced-stage disease.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Morotti et al reported that serum CA 125 level was elevated in 24-61% of patients with SBOT 16 . In the study of Xie et al 14 , 83.3% of patients with SSPBOT presented with variously high levels of CA 125. The difference may be attributable to the varying proportions of patients with advanced-stage disease.…”
Section: Discussionmentioning
confidence: 92%
“…reported that serum CA 125 level was elevated in 24–61% of patients with SBOT 16 . In the study of Xie et al 14 ,. 83.3% of patients with SSPBOT presented with variously high levels of CA 125.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations